PENGEMBANGAN MODEL PEMBELAJARAN SENAM LANTAI BERBASIS MULTIMEDIA - Muhammad Suhairi; Awang Roni Effendi; Rajidin Rajidin (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2022)
This study aims to produce interactive multimedia-based floor gymnastics learning media for Jamani Education Study Program students at IKIP PGRI Pontianak in the floor gymnastics course. This study uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Develop, Implement, and Evaluate). Determination of the subject in this study was done with a purposive sample. Informants from the development research carried out consisted of 2 experts, namely; material experts and media experts, small group trials of physical education study students with a total of 20 students as subjects, and large group trials of 40 physical education study students who took floor gymnastics courses. Research data obtained from; product validation design, giving small-scale test questionnaires and large-scale tests. The results showed that the interactive multimedia learning media for floor exercise can be used by teachers and students easily to understand the learning material for floor gymnastics with a very good response.AbstrakPenelitian ini bertujuan untuk menghasilkan media pebelajaran senam lantai berbasis multimedia interaktif untuk mahasiswa Prodi Pendidikan Jamani di IKIP PGRI Pontianak pada mata kuliah senam lantai. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan ADDIE (Analysis, Design, Develop, Implement, dan Evaluate). Penentuan subjek dalam penelitian ini dilakukan dengan puposive sample. Informan dari penelitian pengembangan yang dilakukan terdiri dari 2 ahli yaitu; ahli materi dan ahli media, uji coba kelompok kecil dari mahasiswa prodi pendidikan jasmani dengan jumlah sabjek 20 mahasiswa, dan uji coba kelompok besar berjumlah 40 mahasiswa prodi pendidikan jasmani yang mengikuti mata kuliah senam lantai. Data hasil penelitian diperoleh dari; desain validasi produk, pemberian angket uji skala kecil dan uji skala besar. Hasil penelitian menunjukkan bahwa media pembelajaran multimedia interaktif senam lantai dapat digunakan oleh pengajar dan mahasiswa secara mudah untuk memahami materi pembelajaran senam lantai dengan respon sangat baik.